2007
DOI: 10.1176/appi.ps.58.3.378
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress Among Latino Family Caregivers of Adults With Schizophrenia: The Roles of Burden and Stigma

Abstract: Objective-Little research has focused on the mental health of Latino caregivers with a relative with schizophrenia, despite data showing that up to three-quarters of Latino persons with schizophrenia live with their families. This study examined the relation between caregivers' mental health and perceived burden and stigma and characteristics of the patient and caregiver.Methods-Interviews were conducted in the language of preference (Spanish or English) in Wisconsin, California, and Texas with 85 Latinos cari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
3
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 20 publications
(31 reference statements)
7
63
3
1
Order By: Relevance
“…In other words, the meaning making that religion offers appear to improve the quality of patients’ lives. Greater religiosity was also found to be correlated with less depression and better self-esteem and self-care in several studies of caregivers of patients with mental illness (e.g., Magaña, Ramirez, Hernandez, & Cortez, 2007; Murray-Swank, et al, 2006). …”
Section: The Effect Of a Culturally-informed Therapy On Self-conscioumentioning
confidence: 74%
See 1 more Smart Citation
“…In other words, the meaning making that religion offers appear to improve the quality of patients’ lives. Greater religiosity was also found to be correlated with less depression and better self-esteem and self-care in several studies of caregivers of patients with mental illness (e.g., Magaña, Ramirez, Hernandez, & Cortez, 2007; Murray-Swank, et al, 2006). …”
Section: The Effect Of a Culturally-informed Therapy On Self-conscioumentioning
confidence: 74%
“…Department of Health and Human Services, 2001) and do not take into account factors that may be important for different cultural groups. As a result, these programs may be less relevant for ethnic/racial minority groups, who overwhelmingly report turning to spiritual and collectivistic values when coping with mental illness (Magaña et al, 2007). Additionally, evidence suggests that these values, which are more common among minorities, may encourage more supportive family environments and a healthier environment for the patient.…”
Section: Methodsmentioning
confidence: 99%
“…We chose psychosis, as it touches a number of disorders (schizophrenia, bipolar disorder, major depression, dementia, and substance abuse) and is associated with considerable burden to family caregivers (Magaña, Ramirez Garcia, Hernandez, & Cortez, 2007) and society overall (Wu et al, 2005). Moreover, psychotic symptoms may be more easily understood by lay persons than clinical conditions that require attention to fine-grained diagnostic distinctions.…”
Section: Psychosis Literacymentioning
confidence: 99%
“…Mental illness carries a heavy stigma for both the individual and the family. For instance, Magaña et al (2007) found that Latino caretakers of an adult within the family diagnosed with schizophrenia reported their level of distress to be associated with how negatively they thought others perceived them for having a mentally ill family member. Others have also found more negative attitudes toward mentally ill individuals in Latino populations relative to white non-Latinos.…”
Section: Cultural Influences In Meaning and Expressionmentioning
confidence: 99%